Electoral accountability, responsibility attributions, and the democratic deficit in devolved Wales - Dafydd, Einion and Badanjak, Sanja (Parliamentary Affairs: A Journal of Representative Politics 5)
This study explores electoral accountability at the devolved level in Wales. The retrospective voting model assumes that electoral accountability requires that citizens assign responsibility accurately and vote on the basis of their evaluation of government performance. Drawing on data from the 2016 Welsh Election Study, we examine whether citizens in Wales can identify devolved policy competences and office holders, and identify factors that are linked to accurate attributions. We then examine whether voters seek to use devolved elections as a sanctioning tool, even if they do not have the information required to do so accurately. The findings indicate that there is an acute accountability deficit at the devolved level in Wales: few have the knowledge or the inclination to hold those in power to account. The conclusion discusses the implications of these findings for democracy in Wales and in other multi-level settings.- Reproduced
Keywords: Electoral accountability, Electoral responsibility, Electoral attributions, Democratic deficit, Wales